STUDI ANALISIS GENDER TERHADAP MATERI FIQH PEREMPUAN PADA PENGAJIAN MAJELIS TAKLIM SE-KOTA PAREPARE - Rahmawati, Rahmawati; Rukiah, Rukiah; Basri, Hj. Rusdaya (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2016)
Contextualization fiqh women are more dominant on fiqh issues including family muamalah. Therefore, knowledge and experience possessed religious different then the understanding is quite varied and patterned into a semi - contextual, contextual and contextual moderate liberal. When viewed from a gender committee analysis of the understanding of women in the teaching of fiqh in the town of Parepare yet or no impact on the birth manipestasi gender inequality. Eventhoughthere is a difference between the law of men and women in the areas of worship mahdah and can not be understood contextually but it does not potentially give injustice.Implementation of the study fiqh women basically do not lead to the birth of a gender gap. However manipestasi gender inequality is mainly a culture or tradition of women who have been accustomed charged domestic roles. As a result , the role of dual or double burden always looked at relationships between men and women in the family. Such as the role of domestic and child education played a more dominant women/mothers.